CD271(+) Subpopulation of Pancreatic Stellate Cells Correlates with Prognosis of Pancreatic Cancer and Is Regulated by Interaction with Cancer Cells - Fujiwara, Kenji (Public Library of Science, 2012)
Pancreatic stellate cells (PSCs) play a crucial role in the aggressive behavior of pancreatic cancer. Although heterogeneity of PSCs has been identified, the functional differences remain unclear. We characterized CD271(+) PSCs in human pancreatic cancer. Immunohistochemistry for CD271 was performed for 31 normal pancreatic tissues and 105 pancreatic ductal adenocarcinomas (PDACs). We performed flow cytometry and quantitative RT-PCR, and assessed CD271 expression in PSCs isolated from pancreatic tissues and the changes in CD271 expression in PSCs cocultured with cancer cells. We also investigated the pattern of CD271 expression in a SCID mouse xenograft model. In the immunohistochemical analyses, the CD271-high staining rates in pancreatic stroma in normal pancreatic tissues and PDACs were 2/31 (6.5%) and 29/105 (27.6%), respectively (p = 0.0069). In PDACs, CD271(+) stromal cells were frequently observed on the edge rather than the center of the tumors. Stromal CD271 high expression was associated with a good prognosis (p = 0.0040). Flow cytometric analyses demonstrated CD271-positive rates in PSCs were 0–2.1%. Quantitative RT-PCR analyses revealed that CD271 mRNA expression was increased in PSCs after coculture with pancreatic cancer cells. However, the level of CD271 mRNA expression subsequently decreased after the transient increase. Furthermore, CD271 mRNA expression was decreased in PSCs migrating toward pancreatic cancer cells through Matrigel. In the xenograft model, CD271(+) PSCs were present at tumor margins/periphery and were absent in the tumor core. In conclusion, CD271 was expressed in PSCs around pancreatic tumors, but not in the center of the tumors, and expression decreased after long coculture with pancreatic cancer cells or after movement toward pancreatic cancer cells. These findings suggest that CD271(+) PSCs appear at the early stage of pancreatic carcinogenesis and that CD271 expression is significantly correlated with a better prognosis in patients with PDAC.